A camera trap record of scavengers at a kudu carcass: implications for archaeological bone accumulations. Issue 3 (1st September 2020) - Wadley, Lyn
Abstract : A camera trap was set near a greater kudu bull carcass for 3 weeks at the start of winter. The carcass lay in an open savanna setting on a game farm in Limpopo, and it was visited by leopard, brown hyena, black-backed jackal, African civet, honey badger, bushpig and warthog. At the end of a month there were no visible remains of the carcass save the skull and damaged horns. After a week, when decomposition was pronounced, suids spent more time at the carcass than other animals. They may have been responsible for much of the on-site bone consumption. Bone and meat portions not eaten directly at the death scene were probably carried away by scavengers like brown hyena and jackal. The area was excavated and sieved to collect bone debris that might have been trampled into sediment. Only a few small bone fragments were recovered, one of which had a tooth mark. Several outcomes are of interest to archaeologists. Firstly, the diversity of scavengers at the kudu carcass (including some animals not normally classified as scavengers) suggests that damage on surviving bone at some archaeological sites may be from an assortment of animals not normally considered to be scavengers. Comparative collections must accommodate such variety. Secondly, under certain environmental conditions, death assemblages in the wild may disappear without trace when predators can move freely and feed without disturbance. Thirdly, is possible that some bone fragments survive at archaeological sites because they were protected (possibly unintentionally) by human presence, and because they were on occasion processed in ways that made them less attractive to predators.